Sammlung = Collection Marta Herford 01 - Hoet, Jan; Kröger, Michael; Marta Herford, Herford (Herford : MARTa Herford, 2005)
Albrecht, Susanne ; Art & Language ; Atelier van Lieshout ; Balkenhol, Stephan ; Bratkov, Sergey ; Buckingham, Matthew ; Cai Guo-Qiang ; Chiasera, Paolo ; Czosnowska, Monika ; Danke, Raphael ; Danke, tobias ; Escher, Jürgen ; Fogli, Andrea ; Geers, Kendell ; Gröting, Asta ; Gubbels, Klaas ; Huber, Thomas ; Hullegie, Nick ; Hutter, Robert ; Kusolwong Surasi ; Lohaus, Bernd ; Maganias, DeAnna ; Melgaard, Bjarne ; Morellet, François ; Mucha, Reinhard ; Mwangi, Ingrid ; Op de Beeck, Hans ; Panamarenko ; Pernice, Manfred ; Rentmeister, Thomas ; Ronsse, Matthieu ; Rosenbohm, Lars ; Sailstorfer, Michael ; Sasnal, Wilhelm ; Schatz, Silke ; Schmidt, Erik ; Vanseveren, Hannes ; Solakov, Nedko ; Tayou, Pascale Marthine ; Tunn, Susanne ; Walde, Martin ; Wilson, Robert ; Zwaal-Kallos, Alexandra
Biog., geselect. tent. p. 102-118
Publication on the occasion of the exhibition 'Sammlung = Collection Marta Herford01' im Marta Herford in Herford, 29.10.2005 - 08.01.2006
boek